Developing Phonics Teaching Media and Materials-Based Flip Book - Patria, Lilis; Yuliana, Yohanes Gatot Sutapa; Ikhsanudin, Ikhsanudin (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research aimed to develop an electronic book for teaching phonics. This was a Research and Development (R&D) study with four stages. The subjects of the study were K2 students and K2 teachers of Tunas Bangsa school. The research procedures were adapted from Jolly and Bolitho’s model consisting of identification of need for materials, production of materials, student use of materials, evaluation of materials against agreed objectives. This research data was collected through interview, observation and material aspects validation sheet which are analyzed quantitatively and qualitatively. The materials writing and implementation findings revealed that the materials were considered appropriate and relevant with the students’ and teachers’ needs as they provided specific phonics materials and meaningful activities for K2 students. It was supported by the results from the aspects of the developed materials, which were 3.93, which was in the range of 3.25 < x ≤ 4 and can be categorized as “very good”.